Search for low-mass dilepton resonances in Higgs boson decays to four-lepton final states in proton-proton collisions at s = 13 TeV - Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Valle, A Escalante Del; Frühwirth, R; Jeitler, M; Krammer, N; Lechner, L; Liko, D; Madlener, T; et al. (The European physical journal. C, Particles and fields, 2022)
A search for low-mass dilepton resonances in Higgs boson decays is conducted in the four-lepton final state. The decay is assumed to proceed via a pair of beyond the standard model particles, or one such particle and a Z boson. The search uses proton-proton collision data collected with the CMS detector at the CERN LHC, corresponding to an integrated luminosity of 137 fb - 1 , at a center-of-mass energy s = 13 TeV . No significant deviation from the standard model expectation is observed. Upper limits at 95% confidence level are set on model-independent Higgs boson decay branching fractions. Additionally, limits on dark photon and axion-like particle production, based on two specific models, are reported.